Flood Risk in Szeged before River Engineering Works: A Historical Reconstruction - Szalontai, Csaba (Journal of Environmental Geography, 2016)
Szeged situated at the confluence of the Tisza and the Maros Rivers has been exposed to significant flood risk for centuries due to its low elevation and its location on the low floodplain level. After the Ottoman (Turkish) occupation of Hungary (ended in 1686), secondary sources often reported that the town was affected by devastating floods which entered the area from north, and a great part of the town or its whole area was inundated. Natural and artificial infill reduced the flood risk to some extent after the town had been founded, but in the 19th century flood risk was mitigated by river engineering and the reconstruction of the town. The town relief was raised by a huge amount of sediment, which makes it difficult to determine the elevation of the original relief as well as the exact flood risk of the study area. However, some engineering surveys originating from the 19th century contain hundreds of levelling data in a dense control point network making possible to model the relief of the whole town preceding its reconstruction and ground infill. Based on these data, we prepared a relief model which was compared with the known data of the 1772 flood peak, from which we deduced that 60% of the town must have been inundated before it was filled up. As there could have been 50-100 cm thick natural or artificial ground infill since the 11th century, the original natural relief can be gained by deducting these data. Based on this deduction, the extent of inundation centuries ago could reach 85%, which means almost total flooding.